Seismic effects of the bankruptcy reform - Donald P. Morgan; Benjamin Iverson; Matthew Botsch (Federal Reserve Bank of New York, 2009)
We argue that the 2005 bankruptcy abuse reform (BAR) contributed to the surge in subprime foreclosures that followed its passage. Before BAR, over-indebted mortgagors could free up income to pay the mortgage by filing bankruptcy and having their unsecured debts discharged. BAR blocks that maneuver for better-off filers by way of a means test. We identify the effects of BAR using state home equity bankruptcy exemptions; filers in low-exemption states were not very protected before BAR, so they would be less affected by the reform. Difference-in-difference regressions confirm four predictions implied by that identification strategy. Our findings add to research trying to explain the surge in subprime foreclosures and to a broader literature on household bankruptcy demand and credit supply.
Keywords: G21; G33; K35; 330; Bankruptcy; subprime foreclosures; subprime mortgages; unsecured debt; credit card debt; home equity exemptions; cram-down